2013
DOI: 10.1002/jclp.21977
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Family Profile of Addictive Behaviors? Family Functioning in Anorexia Nervosa and Drug Dependence Disorder

Abstract: The present study suggests that there are differing levels of severity of family disturbances among fathers, mothers, and patients in both anorexia nervosa and drug dependence disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 61 publications
1
9
1
1
Order By: Relevance
“…Therefore, this suggests that impairment in family functioning may be relatively low across this sample. This is somewhat inconsistent with previous research, which has generally found that families of adolescents with AN report greater family functioning impairment in multiple areas compared to community norms and non‐psychiatric controls . The lack of a non‐clinical comparison group in this study and the differences in measures used to assess family functioning across studies limit many direct comparisons to previous research.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Therefore, this suggests that impairment in family functioning may be relatively low across this sample. This is somewhat inconsistent with previous research, which has generally found that families of adolescents with AN report greater family functioning impairment in multiple areas compared to community norms and non‐psychiatric controls . The lack of a non‐clinical comparison group in this study and the differences in measures used to assess family functioning across studies limit many direct comparisons to previous research.…”
Section: Discussioncontrasting
confidence: 81%
“…Family Functioning in Two Treatments for Adolescent Anorexia Nervosa Family functioning is an important but often neglected outcome in the treatment of eating disorders, given consistent reports from patients and their family members of impairment in one or more areas of family functioning compared to community norms [1][2][3] and to non-psychiatric controls. [4][5][6][7][8][9][10] Common areas of family functioning impairment include family cohesion and organization, family conflict, and emotional expression.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the fundamental assumption of the social cognitive model is that behavior is also influenced by external factors, it is also important for research to account for the types of external antecedents that may influence adolescent's SNSs use. Among the different types of external factors, studies have shown that parents play an important role in influencing the outcomes of addictive tendencies and problematic media behaviors in their adolescents and children (Doty & Dworkin, 2014;Valcke et al, 2010;Yu, Kim, & Hay, 2013); this is consistent with findings from developmental psychology, which show how parents' roles and functions are associated with the development of addictive tendencies during adolescence (Baumrind, 1991;Doba et al, 2014;Montgomery, Fisk, & Craig, 2008;Putnick et al, 2008 While there is a growing interest in understanding the role of parents and its link with problematic media use, one area that received significantly less attention is how parent-child relationship may be an antecedent of problematic SNSs use. This study proposes that relationship with parents may be as equally important as existing focus on external factors such as parental mediation.…”
Section: External Antecedents-relationship With Father and Mothersupporting
confidence: 78%
“…While the findings certainly contribute to the overall understanding of what are the antecedents of problematic media behaviors, compulsivity in media use is a complex phenomenon that is often a consequence of both individual and external factors (Andreassen & Pallesen, 2014). This is well documented in existing literature as studies have shown that external factors such as family structure and relationships are related to development of addictive behaviors (A. E. Barrett & Turner, 2006;Doba, Nandrino, Dodin, & Antoine, 2014;J. Xu et al, 2014;Yen, Yen, Chen, Chen, & Ko, 2007).…”
Section: Social Cognitive Modelmentioning
confidence: 80%
“…Spangler commented the study of Steele et al [21] , and raised the question of paternal relevance for attachment development. Their findings indicate that mother's representation contributes to the adolescent's attachment representation.…”
Section: Introductionmentioning
confidence: 99%